International Regulation of Environmental Auditing in the Countries of the European Union - ZHATKANBAYEVA, Aizhan E.; TUYAKBAYEVA, Nazgul S.; JANGABULOVA, Araylym K.; ALIBEKOV, Sailaubek T.; KASATKINA, Elena V.; MASLIHOVA, Elena A. (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018, 2019)
In the context of the global environmental crisis that is currently one of the most real threats to the existence of mankind the protection and improvement of the quality of the environment is recognized as a world-wide task, acquires exceptional importance, and is a necessary condition for preserving the health, well-being and economic prosperity of the present and future generations of people. The authors note that the recognition of the global nature of environmental problems by the scientific and political elites of the world's leading countries and their associations, among which one of the most influential and powerful is the European Union, calls for intensified cooperation at the international level to adjust existing and develop new approaches to environmental protection, creation of effective mechanisms for the implementation of the newest environmental policy. These factors contribute to the formation of a new philosophy and practice of European economic interaction based on the need for assistance from stronger participants in the world economy to be weak in solving the interrelated tasks of the economy and ecology.